International Willingness to Pay for the Protection of the Amazon Rainforest - Siikamaki, Juha V.; Krupnick, Alan; Strand, Jon; Vincent, Jeffrey R. (World Bank, Washington, DC, 2019)
The Amazon rainforest, the world's largest tropical rainforest and an important constituent of the global biosphere, continues degrading by rapid deforestation, which is expected to continue despite policies to prevent it. Current international funding to protect the Amazon rainforest focuses on benefits from reduced carbon emissions. This paper examines an additional rationale for Amazon protection: the valuation of its biodiversity and forests as natural heritage to the international community. To measure the economic value of this benefit, the paper examines U.S. and Canadian households' willingness to pay to help finance Amazon rainforest protection. The analysis finds that mean willingness to pay to avoid forest losses projected to occur by 2050 despite current protective policies is $92 per household per year. Aggregating across all households and considering the area protected, the analysis finds that preserving the Amazon rainforest is worth $3,168 per hectare (95-percent confidence interval $1,580-$4,756), on average, to households in the United States and Canada. Considering households in other developed countries would generate yet larger estimates of aggregate value, likely comparable to the carbon benefits from rainforest protection. The results reveal high values of the Amazon rainforest to people geographically distanced from it, lending support to international efforts to reduce deforestation in the Amazon.